Measurement of interphase forces based on dual-modality ERT/DP sensor in horizontal two-phase flow gas-water. (March 2019) - Fang, Lide; Wang, Peipei; Zeng, Qiaoqiao; Li, Mingming; Li, Xiaoting; Wang, Mi; Faraj, Yousef; Wang, Qiang
Highlights: Theoretical model for interphase force in gas-water two-phase flow was established. Effects of differential pressure and void fraction on interphase force was analyzed. Developed a dual-modality system to measure differential pressure and void fraction. The system was used to provide a quantitative evaluation of interphase forces. Abstract: In order to better understand the mechanisms of two-phase flow and the prevailing flow regimes in horizontal pipelines, the evaluation of interphase forces is paramount. This study develops a method to quantitatively estimate the interphase force in two-phase gas-water flow in horizontal pipeline. The electrical resistance tomography technology is used to measure the void fraction, while the differential pressure perpendicular to the horizontal pipe is measured in different flow patterns via a Differential Pressure sensor. The inner pipe diameter is 50 mm, the water flow range from 3.26 m 3 /h to 7.36 m 3 /h, the gas flow rate range from 1 to 60 l/min, which covered a range of flow patterns, the absolute pressure range from 0.07 MPa to 0.12 MPa. The relationship between the differential pressure drop and interphase force is established, and the effects of these forces on the flow are analyzed. Experimental results indicate that the dual-modality measurement system was successfully provided a quantitative evaluation of interphase forces in two-phase horizontal gas-water flow.